Germinação de cariopses e identificação de híbridos em cruzamentos de cana-de-açúcar - Ribeiro, Maria Lícia Fonseca (2016)
The sugarcane (Saccharum spp.) is a crop of great influence in Brazilian economy due the utilization of raw for sugar and alcohool production, besides the elevated energetic potential and as renewable souce of energy. The breeding programs have contributed to the achievement of superior cultivars, however, after the crosses; one of the challenges is the production of viable caryopses to achieve clones which will be selected subsequently. Thus, two challenges need further studies, first allow most cariopsis from controlled crossings obtain higher percentage of germination, and secondly prove the hybridization of these crossings. The aim of this study was to evaluate the influence of controlled imbibition on cariopsis germination; and to estimate the genetic diversity through SSR markers and validate the use of ISSR markers in identifying hybrids. The germination of cariopsis of sugarcane submitted to treatment with polyethyleneglycol 6.000 in potential -0.6 and -0.8 MPa were higher than the control, thereby imbibition controlled of the cariopsis can be used to obtain germination performance and seedling establishment. Regarding the use of molecular markers, we observed the presence of the parental alleles in some offspring percentage and genetic variability among crosses; it is possible to use SSR markers in breeding programs for identifying hybrids in biparental crossings.